THE INFLUENCE OF PERCEIVED ORGANIZATION SUPPORT (POS) ON JOB SATISFACTION - Wibisana, Anindita; Putranto, Nur Arief Rahmatsyah (Journal of Business and Management, 2017)
Abstract. Background: This research aims to find out the influence of perceived organizational support to job satisfaction components with the respondents from PT Global Transportation’s taxi-bike drivers. It is important to know the relationship of perceived organizational support to job satisfaction as one common predictor of employee turnover rate.  Methods: This research uses classical assumptions and multiple linear regressions to discover the relationship of perceived organizational support and job satisfaction components Results: finding the relationship and significance of perceived organization support to job satisfaction components.  Conclusion: This research finding the influence of perceived organizational support on the components of job satisfaction and give suggestion regarding on perceived organizational support Keywords:  perceived organization support, job satisfaction, online-based transportation.